2011
DOI: 10.1096/fj.11-185579
|View full text |Cite
|
Sign up to set email alerts
|

Neuritogenesis: the prion protein controls β1 integrin signaling activity

Abstract: Cytoskeleton modifications are required for neuronal stem cells to acquire neuronal polarization. Little is known, however, about mechanisms that orchestrate cytoskeleton remodeling along neuritogenesis. Here, we show that the silencing of the cellular prion protein (PrP(C)) impairs the initial sprouting of neurites upon induction of differentiation of the 1C11 neuroectodermal cell line, indicating that PrP(C) is necessary to neuritogenesis. Such PrP(C) function relies on its capacity to negatively regulate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
148
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(156 citation statements)
references
References 66 publications
4
148
0
4
Order By: Relevance
“…While previous prion studies have pointed to laminin receptors as possible prion protein interaction receptors 36 we show that more specifically the integrin receptors may be linked to PrP C stimulation of neuronal cells, a result recently reported elsewhere. 33 Meanwhile, PrP C stimulation by the 6H4 antibody displayed a distinct signaling repertoire of which the strongest indicators pointed to insulin receptor/MAPK related signaling. While there is cross treatment signaling that is common to both, such as iNOS, the majority of signaling is unique to each treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While previous prion studies have pointed to laminin receptors as possible prion protein interaction receptors 36 we show that more specifically the integrin receptors may be linked to PrP C stimulation of neuronal cells, a result recently reported elsewhere. 33 Meanwhile, PrP C stimulation by the 6H4 antibody displayed a distinct signaling repertoire of which the strongest indicators pointed to insulin receptor/MAPK related signaling. While there is cross treatment signaling that is common to both, such as iNOS, the majority of signaling is unique to each treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Integrin binding to the actin cytoskeleton might impose constraints to the lateral mobility of integrins and reduce avidity. In addition, PrP-silencing has previously been shown to stabilize actin filaments in neuronal cells through a RhoA-dependent pathway (Loubet et al, 2012). Therefore, we explored RhoA activation in shCtrl-and shPrP-U937 cells stimulated with CXCL12 or PMA.…”
Section: Prp Regulates Rhoa Activation and Actin Polymerizationmentioning
confidence: 98%
“…It has been shown previously that the RhoA-regulated actinsevering protein cofilin 1 is involved in the regulation of actin microfilament stability by PrP in neurons (Loubet et al, 2012). To determine whether this pathway is operational in monocytes, we determined the levels of phosphorylated (inactive) cofilin 1 in cells adhering to immobilized Fc-VCAM.…”
Section: Prp Regulates Rhoa Activation and Actin Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The prion protein's role in a particular cellular process, including those that are concerned with metal-PrP interrelations in ex-vivo and in-vivo systems are generally studied by either genetically ablating (Büeler et al, 1992;Haigh and Brown, 2006;Kim et al, 2005;Kuwahara et al, 1999;Rossi et al, 2001;Sakaguchi et al, 1996) or siRNA silencing (Loubet et al, 2012) while working on HeLa cells (Molnár et al, 2013)., and have used here similarly. The bright red immunofluorescence-staining pattern in the ZW 13-2 cells revealed that the prion protein was distributed on the surface of the cells, whereas no immunoreactivity was detected in the Zpl 2-1 cells.…”
Section: Resultsmentioning
confidence: 99%